The prevalence and risk factors of stroke in patients with chronic schizophrenia - Liang Y (Dove Medical Press, 2016)
Ying Liang,1 Jian Huang,1 Jingbin Tian,2 Yuanyuan Cao,2 Guoling Zhang,2 Chungang Wang,2 Ying Cao,2 Jianrong Li2 1National Clinical Research Center for Mental Disorders, Peking University Sixth Hospital, Institute of Mental Health, Key Laboratory of Mental Health, Ministry of Health, Peking University, 2Changping Traditional Chinese Medicine Hospital, Beijing, People’s Republic of China Objective: To investigate the stroke risk and risk factors in patients with chronic schizophrenia.Patients and methods: This study was a large-sample, cross-sectional survey. A total of 363 patients with chronic schizophrenia were selected from the Changping Traditional Chinese Medicine Hospital, Beijing, in August 2014. The patients were divided into either stroke group or control group based on the presence of stroke. Clinical evaluation included positive and negative syndrome scale assessment and a detailed questionnaire to collect the general information and disease-related conditions.Results: The prevalence of stroke was 16.5% (60 cases). Stroke and control groups showed a significant difference in age, sex, smoking, combined medication, doses, negative factor score in positive and negative syndrome scale, body mass index, waist circumference, and systolic blood pressure. Multivariate analysis showed that a number of factors are significantly related to stroke, including age, sex, smoking, combined medication, doses, body mass index, and systolic blood pressure.Conclusion: The prevalence of stroke is relatively higher in Chinese patients with chronic schizophrenia. Chronic schizophrenia patients are more likely to suffer from stroke; meanwhile, a number of risk factors were identified, including old age, female sex, smoking history, combined medication with a variety of drugs, high doses, obesity, and high blood pressure. Keywords: schizophrenia, stroke, risk, risk factors